THE INFLUENCE OF SELF-EFFICACY AND LOCUS OF CONTROL ON EMPLOYEE PERFORMANCE WITH JOB SATISFACTION AS AN INTERVENING VARIABLE ON CLEANING OFFICERS AT THE YOGYAKARTA CITY TRADE SERVICE - Kelik Novidwyanto Wibowo; Kusuma Chandra Kirana; E. Didik Subiyanto (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
This study aims to analyze the effect of self-efficacy and locus of control on employee performance with job satisfaction as an intervening variable on Cleaning Officers of the Yogyakarta City Trade Service. This study uses a quantitative approach with a census method of 140 cleaning officers. The data analysis technique used is Partial Least Square - Structural Equation Modeling (PLS-SEM) with the help of SmartPLS software. The results of the study indicate that self-efficacy does not have a significant effect on job satisfaction or employee performance. On the contrary, locus of control has a positive and significant effect on both job satisfaction and employee performance. Job satisfaction has also been shown to have a positive and significant effect on employee performance. However, job satisfaction cannot mediate the effect of self-efficacy on employee performance significantly. This finding indicates that locus of control and job satisfaction are more dominant factors in influencing the performance of cleaning officers. The implication of this study is the importance of focusing efforts to improve performance on aspects of self-control (locus of control) and job satisfaction, through employee involvement and the creation of a conducive work climate.